Punitive welfare reform and claimant mental health: The impact of benefit sanctions on anxiety and depression. (11th June 2020) - Williams, Evan
Abstract: Internationally, policymakers assume that sanctioning claimants of unemployment benefits will engender both improved employment outcomes and wider positive effects. A growing evidence‐base challenges these expectations, though additional insight is needed from large‐scale longitudinal research. This article contributes by conducting a quantitative investigation into the mental health impacts of benefit sanctions. To do so, it focuses on a recent period in UK sanctions policy in which rates of sanctions varied markedly and their length was substantially increased. Using quarterly panel data for local authorities in England (Q3 2010–Q4 2014) and fixed effects models that control for important confounders, the analysis provides robust evidence that Jobseeker's Allowance (JSA) sanctions lead to increases in self‐reported anxiety and depression. Evidence of this adverse impact is particularly clear following the increase in the length of sanctions in October 2012. The results have important implications for contemporary social security policy, which is underpinned by a similarly punitive sanctions regime. Whilst additional individual‐level research is needed to fully consider the causal relationships in operation, the findings support a precautionary approach that should seek to minimise the harm associated with sanctions. This implies taking steps to reduce both the severity and frequency of applied sanctions.